A expressão é equivalente a qual resposta?
Anexos:
![](https://pt-static.z-dn.net/files/d11/5f519fb7be7911b31601af406e89b5a3.png)
Soluções para a tarefa
Respondido por
2
Explicação passo-a-passo:
(x+1).(x-1)= x² -1
Substituir:
(x+1).(x-1)/5(x+1)÷2(x-1)/20x=
(x-1)/5 × 20x /2(x-1)=
20x/10=
2x
Anexos:
![](https://pt-static.z-dn.net/files/da4/953aafc468f1849629707aa97f23bca0.jpg)
Respondido por
2
Resposta:
2×
Explicação passo-a-passo:
(×+1).(×-1)=ײ-1
(×+1).(×-1)/5(×+1)÷2(×-1)/20×=
(×-1)/5×20×/2(×-1)=
20×/10
RESPOSTA: 2×
Perguntas interessantes
Ed. Física,
10 meses atrás
Química,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Física,
1 ano atrás